Daniel Nikolaus Chodowiecki - Bauer, Jens-Heiner,Chodowiecki, Daniel,Dohna-Schlobitten, Alexander zu,Engelmann, Wilhelm (Bauer, 1982)
Oeuvre-Verzeichnis
Oeuvre-Verzeichnis
Keywords: Bildband; Werkverzeichnis